2022
DOI: 10.3390/jcdd9060174
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Outlook on Dilated Cardiomyopathy (DCM): State-Of-The-Art Developments with Special Emphasis on OMICS-Based Approaches

Abstract: Dilated cardiomyopathy (DCM) remains an enigmatic cardiovascular disease (CVD) condition characterized by contractile dysfunction of the myocardium due to dilation of the ventricles. DCM is one of the major forms of CVD contributing to heart failure. Dilation of the left or both ventricles with systolic dysfunction, not explained by known causes, is a hallmark of DCM. Progression of DCM leads to heart failure. Genetic and various other factors greatly contribute to the development of DCM, but the etiology has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 146 publications
0
5
0
Order By: Relevance
“…[20][21][22] An important component of acute myocarditis is apoptosis seen in cardiomyocytes, which is considered to be the main pathology leading to DCM or HF. 23 In an experimental autoimmune myocarditis study, it is observed that the cholesterol efflux mechanisms of cardiomyocytes are impaired. The inflammatory process is observed to be regressed and cardiac functions improved, following draining of cholesterol out of the cardiomyocytes by a cholesterol depleting agent, called methyl -β-cyclodextrin.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] An important component of acute myocarditis is apoptosis seen in cardiomyocytes, which is considered to be the main pathology leading to DCM or HF. 23 In an experimental autoimmune myocarditis study, it is observed that the cholesterol efflux mechanisms of cardiomyocytes are impaired. The inflammatory process is observed to be regressed and cardiac functions improved, following draining of cholesterol out of the cardiomyocytes by a cholesterol depleting agent, called methyl -β-cyclodextrin.…”
Section: Discussionmentioning
confidence: 99%
“…Others are found in LMN, DES, VCL (Vinculin), TTR (transthyretin), BAG3 (associated with apoptosis), MT-TS2 (encoding a mitochondrial small RNA), or transcription factor encoding PRDM16 [74][75][76][77][78]. In adult and pediatric DCM, the same genes seem to be affected, though unfortunately, most genetic testings have been performed in adults [79]. Besides the genetic causes, inflammation may lead to DCM, the main non-genetic cause in children.…”
Section: Cellular Compartments Affected By Genetic Mutations Causing ...mentioning
confidence: 99%
“…BNP (B-type natriuretic peptide) is predominantly synthesized by LV cardiomyocytes as a protective mechanism against pressure or volume overload ( Cao et al, 2019 ; Okamoto et al, 2019 ). BNP mimics ventricular stress by decreasing the kidney tubule vascular resistance and increasing GFR ( Okamoto et al, 2019 ; Sarohi et al, 2022a ). However, hyperactivation of RAAS and SNS inhibit the BNP activity and worsens the condition ( Okamoto et al, 2019 ).…”
Section: Clinically Available Biomarkers For Acute Crsmentioning
confidence: 99%